Thermal-physical analysis of low-radioactive thermonuclear plasma in the magnetic fusion device - Ryzhkov, S.V. (Вопросы атомной науки и техники, 2007)
A field-reversed configuration (FRC) plasma is vortex-like, isolated toroid of plasma with high beta (plasma pressure/magnetic-field pressure). Such a self-organized, stable system is a candidate for the magnetic fusion confinement. The proposal of a compact toroid as fusion reactor together with advanced fuel is based on the low radioactivity of deuterium-helium-3 plasma. Analysis of conceptual parameters of the D-³He and D-T FRC power plant was carried out. Advantages and disadvantages of the D-³He reaction, problem of ³He acquisition and advanced fuels prospects are discussed.